Pemanfaatan Literasi Digital Dalam Proses Pembelajaran Program Kesetaraan Paket C di PKBM Sunan Kalijaga Kota Kediri - Al Agustin, Leo Khoiriyah; Indrianti, Deditiani Tri; Purnamawati, Frimha (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
Learning citizens must be able to use and understand things related to digital technology, this is what is called digital literacy. The purpose of this study is to identify and describe the use of digital literacy in PKBM Sunan Kalijaga. This study uses a descriptive type of research with a qualitative approach. The research location is in PKBM Sunan Kalijaga, selected using the purposive area technique. The technique of determining informants is purposive sampling and to complete the data by selecting the category of informants using snowball sampling. Data collection techniques using interviews, observation, and documentation. Data validity checking technique using increased persistence and triangulation. Data analysis used the theory of Miles and Huberman with data collection, data reduction, data presentation, and conclusions. The results showed that at PKBM Sunan Kalijaga literacy used the SetaraDaring application as a learning medium. Because this application was developed for distance learning equivalence education and features are complete and detailed, such as: module material, communication, assignments, exams, assessments, attendance, and virtual learning